AAS and XRD Analysis of Gold Ore Bioflotation Results with Aloe Vera as an Environmentally Friendly Reagent - Mantika, Sabrina; Prillasasti, Farra Diva; Nugrah Aurigha, Evan; Amelia, Rike; Rickiadi, M. Fajar; Wahyuningsih, Tri (Journal of Metallurgical Engineering and Processing Technology, 2024)
Flotation is a mineral concentration method that involves floating the minerals so that they can be separated from the gangue by the addition of reagents. The reagents used are chemicals such as frother and collector, which can potentially contaminate the environment. This research explores the potential use of aloe vera as a separating reagent in environmentally friendly gold ore flotation. The feed used consists of 300 grams of gold ore, and the flotation time is set at 15 minutes. XRD analysis is employed to determine the types of minerals contained in the sample, revealing that the sample consists of 97.64% quartz; Enstatite, syn 1.21%; and Clinochlore-1A 1.16%. Atomic Absorption Spectrophotometry (AAS) is the technique used to determine the metal concentration in a sample. AAS analysis indicates an Au concentration in the feed of 3.94 ppm. The Au concentration in the concentrate with the addition of aloe vera extract is 10.57, and in the tailings, it is 0.92, higher than the concentration in the concentrate without the addition of aloe vera extract, which is 10.11, with 1.89 in the tailings. The %recovery from these concentrations with the addition of aloe vera extract is 84.06%, while without the addition of aloe vera extract, it is 63.78%. This study provides evidence that the use of aloe vera in the gold ore flotation process can be a sustainable and environmentally friendly alternative in the effort to improve the separation of valuable minerals from impurities.